2022
DOI: 10.3390/ijms23063249
|View full text |Cite
|
Sign up to set email alerts
|

The EPH/Ephrin System in Gynecological Cancers: Focusing on the Roots of Carcinogenesis for Better Patient Management

Abstract: Gynecological cancers represent some of the most common types of malignancy worldwide. Erythropoietin-producing hepatocellular receptors (EPHs) comprise the largest subfamily of receptor tyrosine kinases, binding membrane-bound proteins called ephrins. EPHs/ephrins exhibit widespread expression in different cell types, playing an important role in carcinogenesis. The aim of the current review was to examine the dysregulation of the EPH/ephrin system in gynecological cancer, clarifying its role in ovarian, endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…53 Abnormal tyrosine metabolism also plays a very important role in the occurrence and development of tumours. 54 GSEA results showed that PPP1R14B was closely related to H3K27me3, PRC2, and other epigenetic genes, which are closely related to the stem cell characteristics of tumour cells. In many poorly differentiated tumours, the stem cell phenotype is often very obvious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Abnormal tyrosine metabolism also plays a very important role in the occurrence and development of tumours. 54 GSEA results showed that PPP1R14B was closely related to H3K27me3, PRC2, and other epigenetic genes, which are closely related to the stem cell characteristics of tumour cells. In many poorly differentiated tumours, the stem cell phenotype is often very obvious.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the enrichment of retinol metabolism and tyrosine metabolism has been observed, and retinol and its derivatives can effectively delay or prevent precancerous lesions and induce tumour cell differentiation and apoptosis 53 . Abnormal tyrosine metabolism also plays a very important role in the occurrence and development of tumours 54 . GSEA results showed that PPP1R14B was closely related to H3K27me3, PRC2, and other epigenetic genes, which are closely related to the stem cell characteristics of tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest subfamily of RTKs is represented by the Eph (Erythropoietin-producing hepatocellular) receptors that interact with membrane-bound ligands called ephrins [ 97 , 98 ]. EphA1 was the first discovered Eph receptor tyrosine kinase and was cloned in 1987 from a hepatocellular carcinoma (HCC) cell line; next, in 1990 the screening of a cDNA library of HeLa cells brought the identification of EphA2 [ 99 , 100 , 101 , 102 ]. Currently, 14 Eph receptors and 8 ephrin ligands are known, there are nine Eph receptors of type-A (EphA1-8, and EphA10) and 5 Eph receptors of type-B (EphB1-4,6).…”
Section: The Epha2 Receptor and Its Controversial Role In Cancermentioning
confidence: 99%
“…OC is the seventh most common gynecological malignancy, with 140,000 deaths per year reported [ 9 , 10 ]. In 2021, 13,770 deaths from OC were documented according to the American Cancer Society [ 11 ]. The vast majority of ovarian tumors are epithelial, which present with vague persistent gastrointestinal and urologic symptoms, such as excessive bloating and discomfort [ 12 ].…”
Section: Introductionmentioning
confidence: 99%